Efficacy of Sodium Chloride as a Taste Additive for Improvement in Bait Acceptance by Rodents - Singla, Neena; Kaur, B; Parshad, V R (Annals of Arid Zone, 2016)
Sodium chloride (coI11Irionsalt) at 0.5, 1.0 and 2.0% concentrations was tested for its efficacy as a taste additive in two kinds of bait base i.e. WSO (cracked wheat, powdered sugar and groundnut oil in 96:2:2) and WO (creacked wheat and groundnut oil in 98:2) in bichoice with plain WSO bait for improvement in bait acceptance by lesser bandicoot rat, Bandicota bengalensis and two body weight groups of house rat, Rattus rattus. Mean daily consumption of both WSO and WO bait bases containing different concentrations of sodium chloride was found to be lower than plain WSObait. Also the mean daily consumption of WSO bait base containing sodium chloride was more than WO bait base containing 'sodium chloride at all the concentrations tested except by R. rattus of higher body weight group at 1.0% and B. bengalensis at 1.0 and 2.0% sodium chloride. Present results suggest lower acceptance of baits containing sodium chloride as compared to those containing sugar by B. benegalensis and R. rattus with some species specific and age specific variations. Key words: Sodium chloride, taste additive, Bandicota bengalensis, Rattus rattus.